Understanding the impact of irrigation scheduling on water use efficiency in corn and soybean production in humid climates: insights from on-farm demonstration - Kelley, Brenden; Dong, Younsuk; Chilvers, Martin I.; Das, Narendra (Frontiers in Agronomy, 2025)
Irrigation plays a key role in boosting crop yields, supporting crop diversity, and reducing the impact of climate variability, especially in regions like the Great Lakes region where seasonal water availability can be unpredictable. Improving irrigation water use efficiency (WUE) is critical for ensuring long-term water sustainability. This study explores water use efficiency (WUE) in southwest Michigan’s humid climate, focusing on improving irrigation management practices. Several different volumes and frequencies of irrigation (30%, 50%, and 60% Maximum Allowable Depletion) were examined as experimental treatments to better understand their impact on crop productivity. Despite testing an array of different experimental irrigation treatments, we found no statistical differences but noted unequal averages and data spreads. These trends suggest more samples, under typical climatic conditions, are needed to distinguish which irrigation approaches enhance WUE. We also contrasted producers’ methods with experimental treatments, highlighting the challenges of optimizing WUE in the region’s climate and soil conditions even with experience in irrigation management. This study was conducted as a demonstration study for the benefit of producers, with the intention of providing a reference for their irrigation management practices.